(untitled) (International Journal of Sustainable Development & World Policy, 2025)
This study investigated the impact of petroleum product pump prices on garri and yam prices in Southwest Nigeria between 2017 and 2022. The study covers the six Southwest states. Data on prices of garri and yam, automotive gas oil, premium motor spirit, and household kerosene, as well as the prices of imported goods and services and the consumer price index, were collated from the National Bureau of Statistics (NBS) fact sheet and Global Data Lab. The data were analyzed using the ordinary least squares technique. Results show that automotive gas oil prices influence the prices of garri and yam in Ogun, Ondo, and Osun; petrol pump prices have a significant influence on the prices of garri and yam in all the states except Osun. Kerosene prices affect the prices of all commodities across all states except Ekiti and Oyo. The consumer price index and imports of goods and services significantly influence the prices of garri and yam in all states except Ekiti. It was concluded that petrol pump prices are the major influencers of garri and yam prices. As a recommendation, adequate implementation of policies aimed at stabilizing petroleum pump prices to mitigate price volatility of essential commodities should be ensured. Mechanisms targeted at cushioning the impact of fluctuating petroleum product prices on raw food affordability should be considered.